Phylogenetic and DNA barcoding study on Dehaasia pugerensis Koord. & Valeton, an endemic and critically endangered species from East Java, Indonesia - Aulia Hasan Widjaya; Andi Salamah; Tety Maryenti; Iyan Robiansyah; Irfan Martiansyah; Muhammad Rifqi Hariri; Weibang Sun (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Dehaasia pugerensis Koord. & Valeton is an endemic plant species classified as critically endangered (CR) in Jember, Java. It thrives in arid, rocky forest regions, making it a significant genetic resource for plant conservation initiatives. This study aimed to analyze the genetics of Dehaasia pugerensis through a molecular approach utilizing DNA (deoxyribonucleic acid) barcoding technique. This experiment utilized three accessions from three populations in Puger Jember, East Java: Igir Pletes (IP), Watu Susu (WS), and Undak Sebanen (US), along with Klatakan (KT). Notably, samples from the WS accession were excluded from internal transcribed spacer (ITS) primers due to poor sequencing results and were substituted with samples from the US accession. A single sample from each population of Dehaasia pugerensis underwent DNA sequencing utilizing DNA barcoding markers from three chloroplast genes: ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL), maturase K (matK), and the transfer RNA-histidine and the photosystem II protein D1 (trnH-psbA) intergenic spacer, as well as one nuclear ITS region. Results Sequence analysis demonstrated identical base composition in the plastid genes rbcL and matK, minor variation in trnH-psbA intergenic spacer, and significant variation in the nuclear ITS region. This demonstrates that the evolutionary rate of the chloroplast genome is lower than that of the nuclear genome. The chloroplast and nuclear genomes exhibit significant differences in evolutionary rates, influenced by various internal and external factors such as inheritance mode, mutation rate, and evolutionary pressures. Phylogenetic analysis indicated that the three accessions clustered together within the same group, as determined by chloroplast genes and ITS region. The three accessions exhibit a close relationship with Dehaasia hainanensis and Dehaasia incrassata, as indicated by the genetic distance observed on the phylogenetic tree. Conclusions DNA barcoding with rbcL, matK, trnH-psbA intergenic spacer, and ITS confirmed the identity of Dehaasia pugerensis and revealed key genetic diversity. Phylogenetic analysis grouped the three accessions (KT450, IP42, WS152) into a single clade, closely related to Dehaasia hainanensis and Dehaasia incrassata, indicating shared evolutionary traits. While rbcL and matK were genetically stable, trnH-psbA intergenic spacer and ITS showed notable variability, particularly in ITS, which revealed important genetic differences. These findings highlight the value of molecular data in shaping conservation strategies for Dehaasia pugerensis, such as propagation, reintroduction, and seed banking.